Low-dimensional quantum dot / nano fluid / solid lubricant composite solid lubricating coating material and preparation method thereof
By adding low-dimensional quantum dots, nanofluids and micron-scale solid lubricating fillers to the coating materials of components such as methanol engine piston rings, a multi-scale filler structure is constructed, which solves the lubrication and wear resistance of methanol engines in high temperature, high humidity and high solvent environments, and achieves a longer service life and better performance.
Patent Information
- Application Number
- CN202411810698.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-25
AI Technical Summary
Moving mechanisms such as methanol engine pistons, bearing shells and piston rings are difficult to meet the requirements of lubrication and wear resistance in high temperature and high humidity environments. The existing polymer solid lubricating coating materials cannot effectively solve the problems of steam and solvent resistance.
Using low-dimensional quantum dot/nano-based fluid/solid lubricant composite materials, the "micro-nano-subnano" multi-scale filler structure is constructed by adding micro-scale polymer solid lubricating fillers, nano-scale rare earth oxide nano-based fluids and sub-nano-level low-dimensional quantum dots to the thermoplastic polyphenylene sulfone modified phenolic resin to construct a "micro-nano-subnano" multi-scale filler structure to improve the self-lubricating, wear resistance and solvent resistance of the coating.
Excellent lubrication and wear resistance in high temperature, high humidity and high solvent environments are achieved, extending the service life of methanol engines, and significantly improving the strength, toughness and self-lubricating properties of the coating material.
Smart Images

Figure CN119684864A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of high molecular polymer solid lubricating coating materials, and in particular to a low-dimensional quantum dot / nano fluid / solid lubricant composite solid lubricating coating material and a preparation method thereof. Background Art
[0003] Methanol is one of the automotive energy sources currently used in small quantities. It has advantages such as green economy and excellent performance in terms of power and emissions. However, methanol engines cannot be completely burned in actual operation, and there will be unconventional emissions such as formaldehyde, formic acid and unburned methanol, which will have adverse effects on the lubrication and friction and wear performance of pistons and piston rings. Polymer solid lubricating coatings are widely used in traditional engine pistons, bearings, piston rings and other moving mechanisms, but it is difficult to meet the technical requirements of methanol engines such as steam resistance and solvent resistance. Summary of the invention
[0004] In view of the deficiencies in the prior art, the object of the present invention is to provide a low-dimensional quantum dot / nano fluid / solid lubricant composite solid lubricating coating material and a preparation method thereof.
[0005] Thermoplastic polyphenylene sulfone resin is extremely resistant to steam and solvents, but due to its linear structure, it cannot work for a long time in harsh environments. Thermosetting phenolic resin has excellent heat resistance and wear resistance. Through the blending and modification of the two, the advantages of the two can be further combined to achieve the purpose of use in special working conditions. Construct a "micron-nano-subnano" multi-scale filler structure in the modified polymer to meet the lubrication and wear resistance of the methanol engine piston ring, piston skirt and other mechanisms, and extend the service life of the methanol engine.
[0006] The objective of the present invention is achieved through the following technical solutions:
[0007] A method for preparing a low-dimensional quantum dot / nano fluid / solid lubricant composite solid lubricating coating material comprises the following steps:
[0008] S1. Adding a polymer solid lubricating filler (micrometer grade) with a particle size of 1-5 μm to a thermoplastic polyphenylene sulfone modified phenolic resin in an amount of 1-20%, and obtaining a mixed slurry A by vacuum high-speed dispersing stirring, grinding, homogenization and other technical means;
[0009] The polymer solid lubricating material is any one or more of polytetrafluoroethylene, ultra-high molecular weight polyethylene, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, polyperfluoroethylene-propylene resin, and ethylene-tetrafluoroethylene copolymer, which functions to reduce the friction coefficient of the modified polymer matrix and improve the self-lubricating performance;
[0010] S2, adding rare earth oxide nanofluid (nanoscale) with a particle size of 10-20 nm to the mixed slurry A in an amount of 0.5-5%, and obtaining a mixed slurry B by vacuum high-speed dispersing stirring, grinding, homogenization and other technical means;
[0011] The rare earth oxide nanofluid is selected from any one or more of cerium oxide nanofluid, yttrium oxide nanofluid, lanthanum oxide nanofluid, etc., and its function is to construct a catalytic transfer membrane;
[0012] S3, adding low-dimensional quantum dots (sub-nanometer level) with a particle size of less than 2 nm to the mixed slurry B in an amount of 0.5-2%, and obtaining a thermoplastic polyphenylene sulfone modified phenolic resin coating material by vacuum high-speed dispersing stirring, grinding, homogenization and other technical means;
[0013] The low-dimensional quantum dots are selected from any one or more of graphite, graphene, molybdenum disulfide, tungsten disulfide, etc., and their function is to improve the strength of the composite material and further improve the friction reduction and wear resistance.
[0014] The amount of filler added in the present invention needs to be strictly controlled within a certain range, this is to further enhance the coating performance, the interface enhancement of the filler and the resin matrix can ensure better adhesion and cohesion in the composite material. Studies have shown that the addition of fillers in an appropriate proportion can significantly reduce the possibility of separation or debonding between the filler and the resin interface, thereby improving the strength, rigidity and toughness of the coating material. However, excessive fillers can destroy the interfacial effect, resulting in a large number of defects in the coating film forming process, generating more holes, and easily generating delamination at the interface, so that the performance tends to decrease. Nano and sub-nano materials are difficult to disperse in resins, so the addition amount cannot be used as a lubricating main material to avoid the performance differences caused by the agglomeration of nanoparticles.
[0015] Furthermore, the stirring is performed using a vacuum high-speed stirrer at a speed of 1000-2000 r / min. Furthermore, the stirring and dispersion is performed at a speed of 1000 r / min for 8 minutes.
[0016] Furthermore, a three-roller grinder is used for grinding. In step S1, the grinding pitch is 5-10 μm and the rotation speed is 350 r / min; in step S2, the grinding pitch is 3-5 μm and the rotation speed is 350 r / min; in step S3, the grinding pitch is 3-5 μm and the rotation speed is 350 r / min.
[0017] Furthermore, the thermoplastic polyphenylene sulfone modified phenolic resin is prepared by the following method: under a nitrogen atmosphere, dissolving a solid thermoplastic polyphenylene sulfone resin in N-methyl-2-pyrrolidone, wherein the mass ratio of the solid thermoplastic polyphenylene sulfone resin to the N-methyl-2-pyrrolidone is 1:4, and stirring and dissolving at a speed of 1000-2000 r / min for 0.5-12h to obtain a liquid thermoplastic polyphenylene sulfone resin with a solid content of 20%; adding a thermosetting phenolic resin with the same mass as the liquid thermoplastic polyphenylene sulfone resin into a three-necked flask, heating to 60-75°C, and stirring at a speed of 1000-2000 r / min; then adding 0.1-2.0% of a reaction catalyst, stirring and reacting for 4-12h to obtain a polyphenylene sulfone modified phenolic resin; the catalyst is dibutyltin dilaurate.
[0018] Furthermore, the rare earth oxide nanofluid is prepared by the following method: first, a certain amount of hydrate of rare earth nitrate compound, polyvinyl pyrrolidone and urea are added to a hydrothermal reactor, and the hydrothermal reaction is carried out at 120-180°C for 6-12 hours, and the obtained product is repeatedly centrifuged, washed, purified and dried; an appropriate amount of organosilicon quaternary ammonium salt hydrolyzed by deionized water is added to the above rare earth oxide, and the reaction is carried out under ultrasonic dispersion for 12-48 hours to obtain modified nano rare earth oxide particles; a certain proportion of modified nano rare earth oxide particles, fatty alcohol polyoxyethylene ether and chloroform are added to a dialysis bag, and the oil bath is heated to 65-75°C for further reaction for 12-48 hours, and the obtained product is dried in a clean vacuum drying oven at a temperature of 60-80°C for 12-48 hours to finally obtain a rare earth oxide nanofluid.
[0019] Furthermore, the low-dimensional quantum dots are prepared by the following method: first, solid particles with a particle size of less than 1 μm are further ground and crushed in an agate mortar; the above solid particles are further crushed and ground in a planetary ball mill for 6-12 hours; the ball-milled particles are put into a strong polar solvent, ultrasonically dispersed for 6-12 hours, and then the supernatant is obtained by a centrifuge; the supernatant is dried in a vacuum drying oven at a temperature of 80-100° C. for 12-48 hours to finally obtain low-dimensional quantum dots.
[0020] Furthermore, the feed ratio of the hydrate of rare earth nitrate compound, polyvinyl pyrrolidone and urea is 1:10:2; the feed ratio of modified nano rare earth oxide particles, fatty alcohol polyoxyethylene ether and chloroform is 10:1:10; the above feed ratios are all mass ratios.
[0021] Furthermore, the rotation speed of the planetary ball mill is 300-500 r / min, argon gas needs to be introduced into the ball mill for protection, and the strong polar solvent is one or more of N-methyl-2-pyrrolidone, N,N-dimethylformamide, dimethylacetamide, etc.
[0022] Furthermore, the diluent used in the mixed slurry is selected from any one or more of N-methyl-2-pyrrolidone, N,N-dimethylformamide, dimethylacetamide, etc.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The low-dimensional quantum dot / nano fluid / solid lubricant composite solid lubricating coating material provided by the present invention is a "micron-nano-subnano" multi-scale filler structure constructed by coupling two new materials, low-dimensional quantum dots and nano fluid, in a thermoplastic polyphenylene sulfone modified thermosetting phenolic resin. By blending and modifying the two high molecular polymer materials, a new material with excellent performance in terms of solvent resistance, high temperature resistance, steam resistance, wear resistance, etc. is obtained. The micron-level high molecular solid lubricating material can significantly reduce the friction coefficient of the modified polymer matrix and improve the self-lubricating performance. The low-dimensional quantum dots have excellent surface effects, can control the entanglement direction and local density of the molecular chain inside the composite material, and provide excellent friction reduction and wear resistance. The solvent-free rare earth oxide nano fluid has liquid-like behavior and can promote the multi-scale synergistic effect of the solid lubricating coating material in the tribochemical reaction process. The solid lubricating coating material of the present invention has excellent strength, toughness and self-lubricating performance, can meet the use under harsh working conditions such as high temperature and humidity, medium load and high speed, and has a wide range of application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the coating morphology after high pressure steam;
[0026] Figure 2 This is the coating morphology after solvent immersion for 24 hours. DETAILED DESCRIPTION
[0027] The present invention is further described below in conjunction with the embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0028] In addition, unless otherwise specified, the preparation processes in the following embodiments are all conventional means in the prior art in the art, and therefore, they are not described in detail.
[0029] Comparative Example 1 Preparation of Thermosetting Phenolic Resin Coating Material
[0030] The unmodified thermosetting phenolic resin was diluted to a viscosity of 1000 cps using N-methyl-2-pyrrolidone at 25°C, and the viscosity was measured by a rotational viscometer. To facilitate the observation of the test results, a trace amount of carbon black powder was added during the material dilution process.
[0031] Comparative Example 2 Preparation of polyphenylene sulfone modified phenolic resin coating material
[0032] The steps are as follows:
[0033] (1) Under a nitrogen atmosphere, a solid thermoplastic polyphenylene sulfone resin is dissolved in N-methyl-2-pyrrolidone, wherein the mass ratio of the solid thermoplastic polyphenylene sulfone resin to the N-methyl-2-pyrrolidone is 1:4, and the mixture is stirred and dissolved at a speed of 1000 r / min for 4 hours to obtain a liquid thermoplastic polyphenylene sulfone resin with a solid content of 20%; a thermosetting phenolic resin having the same mass as the liquid thermoplastic polyphenylene sulfone resin is added to a three-necked flask, heated to 70° C., and stirred at a speed of 1000 r / min; then 1% of a dibutyltin dilaurate reaction catalyst is added, and the mixture is stirred and reacted for 6 hours to obtain a polyphenylene sulfone modified phenolic resin;
[0034] (2) The polyphenylene sulfone modified phenolic resin was diluted with N-methyl-2-pyrrolidone at 25° C. to a viscosity of 1000 cps, as measured by a rotational viscometer.
[0035] Comparative Example 3 Preparation of polytetrafluoroethylene composite polyphenylene sulfone modified phenolic resin coating material
[0036] The steps are as follows:
[0037] 1. Preparation of polyphenylene sulfone modified phenolic resin
[0038] Same as step (1) of Comparative Example 2;
[0039] 2. Preparation of polytetrafluoroethylene composite polyphenylene sulfone modified phenolic resin coating
[0040] (1) Add 10% of the resin mass of polytetrafluoroethylene particles with a particle size of 1 μm to the polyphenylene sulfone modified phenolic resin. Use vacuum high-speed stirring to disperse at a dispersion speed of 1500 r / min, and use a three-roll mill to grind at a grinding interval of 5-10 μm and a speed of 350 r / min. Repeat twice to obtain a mixed slurry A;
[0041] (2) The mixed slurry A was diluted with N-methyl-2-pyrrolidone at 25° C. to a viscosity of 1000 cps, where the viscosity was measured with a rotational viscometer.
[0042] Comparative Example 4 Preparation of Cerium Oxide Nanofluid / Polytetrafluoroethylene Composite Polyphenylene Sulfone Modified Phenolic Resin Coating Material
[0043] The steps are as follows:
[0044] 1. Preparation of polyphenylene sulfone modified phenolic resin
[0045] Same as step (1) of Comparative Example 2;
[0046] 2. Preparation of Cerium Oxide Nanofluids
[0047] First, hexahydrated cerium nitrate, polyvinyl pyrrolidone and urea are added into a hydrothermal reactor in a mass ratio of 1:10:2, and the hydrothermal reaction is carried out at 120°C for 12 hours. The obtained product is repeatedly centrifuged, washed, purified and dried; an appropriate amount of organosilicon quaternary ammonium salt hydrolyzed by deionized water is added to the above cerium oxide, and the reaction is carried out under ultrasonic dispersion for 12 hours to obtain modified nano cerium oxide particles; modified nano cerium oxide particles, fatty alcohol polyoxyethylene ether and chloroform are added into a dialysis bag in a mass ratio of 10:1:10, and the oil bath is heated to 70°C for further reaction for 24 hours. The obtained product is dried in a clean vacuum drying oven at a temperature of 70°C for 24 hours to finally obtain a cerium oxide nanofluid.
[0048] 3. Preparation of cerium oxide nanofluid / solid lubricant polyphenylene sulfone modified phenolic resin coating
[0049] (1) Same as 2.(1) in Comparative Example 3;
[0050] (2) Add cerium oxide nanofluid with a particle size of 10 nm to the mixed slurry A in an amount of 2%. Use vacuum high-speed stirring for dispersion at a dispersion speed of 1500 r / min, and use a three-roll grinder for grinding with a grinding interval of 3-5 μm and a speed of 350 r / min. Repeat twice to obtain a mixed slurry B;
[0051] (3) The mixed slurry B was diluted with N-methyl-2-pyrrolidone at 25° C. to a viscosity of 1000 cps, where the viscosity was measured by a rotational viscometer.
[0052] Comparative Example 5 Preparation of MoS2 Low-Dimensional Quantum Dots / Polytetrafluoroethylene Composite Polyphenylene Sulfone Modified Phenolic Resin Coating Material
[0053] The steps are as follows:
[0054] 1. Preparation of polyphenylene sulfone modified phenolic resin
[0055] Same as step (1) of Comparative Example 2;
[0056] 2. Preparation of MoS2 Low-Dimensional Quantum Dots
[0057] First, the molybdenum disulfide particles smaller than 1 μm are further ground and crushed in an agate mortar; the ground molybdenum disulfide particles are further crushed and ground in a planetary ball mill for 6 hours; the ball-milled particles are put into N-methyl-2-pyrrolidone with a mass ratio of 1:1, and after ultrasonic dispersion for 8 hours, the supernatant is obtained by a centrifuge; the supernatant is dried in a vacuum drying oven at 80°C for 48 hours to finally obtain molybdenum disulfide low-dimensional quantum dots.
[0058] 3. Preparation of MoS2 low-dimensional quantum dots / PTFE-PS modified phenolic resin coating
[0059] (1) Same as 2.(1) in Comparative Example 3
[0060] (2) Adding molybdenum disulfide quantum dots with a particle size of 2 nm to the mixed slurry A in an amount of 2%. Dispersing was performed using vacuum high-speed stirring at a dispersion speed of 1500 r / min, and grinding was performed using a three-roll mill with a grinding interval of 3-5 μm and a speed of 350 r / min. This was repeated twice to obtain a mixed slurry B.
[0061] (3) The mixed slurry B was diluted with N-methyl-2-pyrrolidone at 25° C. to a viscosity of 1000 cps, where the viscosity was measured by a rotational viscometer.
[0062] Example 1 Preparation of MoS2 low-dimensional quantum dots / cerium oxide nanofluid / polytetrafluoroethylene composite polyphenylene sulfone modified phenolic resin coating material
[0063] The steps are as follows:
[0064] 1. Preparation of polyphenylene sulfone modified phenolic resin
[0065] Same as step (1) of Comparative Example 2;
[0066] 2. Preparation of Cerium Oxide Nanofluids
[0067] Same as 2 in Comparative Example 4;
[0068] 3. Preparation of MoS2 Low-Dimensional Quantum Dots
[0069] Same as 3 in Comparative Example 5;
[0070] 4. Preparation of MoS2 low-dimensional quantum dots / Cerium oxide nanofluid / PTFE composite polyphenylene sulfone modified phenolic resin coating
[0071] (1) Same as 2.(1) in Comparative Example 3;
[0072] (2) Same as 3.(2) in Comparative Example 4;
[0073] (3) Adding molybdenum disulfide quantum dots with a particle size of 2 nm to the mixed slurry B in an amount of 2%. Dispersing was performed using vacuum high-speed stirring at a dispersion speed of 1500 r / min, and grinding was performed using a three-roll mill with a grinding interval of 3-5 μm and a speed of 350 r / min. This was repeated twice to obtain a mixed slurry C.
[0074] (4) The mixed slurry C was diluted with N-methyl-2-pyrrolidone at 25° C. to a viscosity of 1000 cps, where the viscosity was measured by a rotational viscometer.
[0075] Example 2 Preparation of MoS2 low-dimensional quantum dots / yttrium oxide nanofluid / polytetrafluoroethylene composite polyphenylene sulfone modified phenolic resin coating material
[0076] The same as Example 1, except that the cerium nitrate hexahydrate in the preparation process of the cerium oxide nanofluid in Example 1 is replaced by yttrium nitrate hexahydrate.
[0077] Example 3 Preparation of graphene low-dimensional quantum dots / cerium oxide nanofluid / polytetrafluoroethylene composite polyphenylene sulfone modified phenolic resin coating material
[0078] The same as Example 1, except that the molybdenum disulfide in the preparation process of the molybdenum disulfide low-dimensional quantum dots in Example 1 is replaced by graphene.
[0079] Example 4 Preparation of MoS2 low-dimensional quantum dots / cerium oxide nanofluid / polytetrafluoroethylene composite polyphenylene sulfone modified phenolic resin coating material
[0080] The same as Example 1, only the addition amount of molybdenum disulfide low-dimensional quantum dots in the mixed slurry was changed to 0.5%, and the addition amount of cerium oxide nanofluid was changed to 0.5%.
[0081] The coating materials prepared in the above comparative examples and embodiments were coated on the surface of the workpiece and cured at high temperature. The curing temperature was 180° C. for 1 hour to obtain samples with lubricating and wear-resistant coatings. Multiple groups were prepared for each sample.
[0082] The samples were tested for tribological properties on an end face friction and wear tester. The wear material was 45# steel with a hardness of 30HRC and a surface roughness of Ra≤0.2μm. The spindle speed was set to 0.6m / s, the load was 1144N, the speed was constant, the load was constant, and the oil lubrication was used to run for 4 hours. The average friction coefficient of the four samples was analyzed.
[0083] Comparing the friction coefficients of the four samples, the friction coefficients of Comparative Examples 1, 2, 3, 4, and 5 are 0.41, 0.18, 0.13, 0.12, and 0.11, respectively. The surface of the sample of Comparative Example 1 is quickly worn, and the surfaces of the samples of Comparative Examples 2, 3, 4, and 5 are slightly worn. The friction coefficients of Examples 1, 2, 3, and 4 are 0.06, 0.04, 0.04, and 0.09, respectively, and no observable wear occurs after the test. The comparison of the friction test results shows that the low-dimensional quantum dot / nano fluid / solid lubricant composite polymer solid lubricant material prepared in the embodiment of the present invention has excellent friction reduction and wear resistance properties under oil lubrication conditions.
[0084] The above samples were placed in a steam sterilizer with a steam temperature of 124°C and a pressure of 100 kPa, and maintained for 30 min. After repeating this three times, the sample morphology was as follows: Figure 1 As shown. It can be observed that in comparative example 1, the unmodified thermosetting phenolic resin exhibited obvious bubbling under the action of high temperature and high pressure steam. Examples 1, 2, 3, and 4 obtained after the resin was modified all maintained their original state under the action of high temperature and high pressure steam. This proves that the modified coating material has excellent high temperature resistance and steam resistance.
[0085] A small amount of methanol solvent was added to the sample surface and allowed to stand for 24 hours. The surface solvent was then wiped off with a non-woven fabric to obtain the solvent resistance of the coating material. Figure 2 It can be observed that the unmodified phenolic resin in Comparative Example 1 has marks, delamination and wrinkles on the coating surface under the action of methanol. The coating materials of Examples 1, 2, 3 and 4 have only a small amount of solvent residue marks or no marks under the action of methanol.
[0086] The test was conducted in accordance with GB / T 6739-2006 "Determination of film hardness by pencil method for paints and varnishes". The test load was 750g. When the tip of the pencil just touched the coating, the test tool was immediately pushed to move at least 7mm, the moving speed was about 1mm / s, and the angle between the pencil and the test plate was 45°. The pencil hardness was tested in the order of HB-1H-2H-3H-4H-5H until the coating was scratched obviously. The test results showed that the pencil hardness of comparative example 1 was 2H, the pencil hardness of comparative examples 2, 3, 4, and 5 was 2H, and the pencil hardness of embodiments 1, 2, 3, and 4 was 3H. This shows that the coating material prepared by the present invention has greatly improved toughness and strength compared with the comparative example.
[0087] Obviously, the described embodiments are only some embodiments of the present invention, but not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A method for preparing a low-dimensional quantum dot / nano fluid / solid lubricant composite solid lubricating coating material, characterized in that: The following steps are involved: S1, adding micron-sized polymer solid lubricating material to thermoplastic polyphenylene sulfone modified phenolic resin, stirring and grinding to obtain mixed slurry A; S2, adding rare earth oxide nanofluid to mixed slurry A, stirring and grinding to obtain mixed slurry B; S3. Add low-dimensional quantum dots to the mixed slurry B, stir and grind to obtain a low-dimensional quantum dot / nano fluid / solid lubricant composite solid lubricant coating material.
2. The method for preparing the low-dimensional quantum dot / nano fluid / solid lubricant composite solid lubricating coating material according to claim 1, characterized in that: The particle size of the polymer solid lubricating material is 1-5 μm; the addition amount of the polymer solid lubricating material is 1-20% of the mass of the thermoplastic polyphenylene sulfone modified phenolic resin; the polymer solid lubricating material is at least one of polytetrafluoroethylene, ultra-high molecular weight polyethylene, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, polyperfluoroethylene-propylene resin, and ethylene-tetrafluoroethylene copolymer.
3. The method for preparing the low-dimensional quantum dot / nano fluid / solid lubricant composite solid lubricating coating material according to claim 1, characterized in that: The particle size of the rare earth oxide nanofluid is 10-20nm; the addition amount of the rare earth oxide nanofluid is 0.5-5% of the mass of the thermoplastic polyphenylene sulfone modified phenolic resin; the rare earth oxide nanofluid is at least one of cerium oxide nanofluid, yttrium oxide nanofluid and lanthanum oxide nanofluid.
4. The method for preparing the low-dimensional quantum dot / nano fluid / solid lubricant composite solid lubricating coating material according to claim 1, characterized in that: The particle size of the low-dimensional quantum dots is less than 2nm; the addition amount of the low-dimensional quantum dots is 0.5-2% of the mass of the thermoplastic polyphenylene sulfone modified phenolic resin; the low-dimensional quantum dots are at least one of graphite, graphene, molybdenum disulfide and tungsten disulfide.
5. The method for preparing the low-dimensional quantum dot / nano fluid / solid lubricant composite solid lubricating coating material according to claim 1, characterized in that: The grinding is performed using a three-roller grinder; in step S1, the grinding spacing is 5-10 μm; in step S2, the grinding spacing is 3-5 μm; in step S3, the grinding spacing is 3-5 μm.
6. The method for preparing the low-dimensional quantum dot / nano fluid / solid lubricant composite solid lubricating coating material according to any one of claims 1 to 5, characterized in that: The thermoplastic polyphenylene sulfone modified phenolic resin is prepared by the following method: dissolving polyphenylene sulfone resin in a solvent to obtain a liquid thermoplastic polyphenylene sulfone resin; adding phenolic resin to the liquid thermoplastic polyphenylene sulfone resin, heating to 60-75° C., adding a catalyst after sufficient stirring, and stirring the reaction for 4-12 hours to obtain a thermoplastic polyphenylene sulfone modified phenolic resin.
7. The method for preparing the low-dimensional quantum dot / nano fluid / solid lubricant composite solid lubricating coating material according to any one of claims 1 to 5, characterized in that: The rare earth oxide nanofluid is prepared by the following method: first, a certain amount of hydrate of rare earth nitrate compound, polyvinyl pyrrolidone and urea are added into a hydrothermal reaction kettle to obtain rare earth oxide through hydrothermal reaction; an appropriate amount of organosilicon quaternary ammonium salt hydrolyzed by deionized water is added into the rare earth oxide, and the reaction is carried out for 12-48 hours under ultrasonic dispersion to obtain modified nano rare earth oxide particles; a certain proportion of modified nano rare earth oxide particles, fatty alcohol polyoxyethylene ether and chloroform are put into a dialysis bag, and the oil bath is heated to 65-75° C. for further reaction for 12-48 hours, and the obtained product is dried in a clean vacuum drying oven at a temperature of 60-80° C. for 12-48 hours to finally obtain the rare earth oxide nanofluid.
8. The method for preparing the low-dimensional quantum dot / nano fluid / solid lubricant composite solid lubricating coating material according to claim 1, characterized in that: The low-dimensional quantum dots are prepared by the following method: first, solid particles with a particle size of less than 1 μm are further ground and crushed in an agate mortar; the solid particles are further crushed and ground in a planetary ball mill for 6-12 hours; the ball-milled particles are put into a strong polar solvent, ultrasonically dispersed for 6-12 hours, and then a supernatant is obtained by a centrifuge; the supernatant is dried in a vacuum drying oven at a temperature of 80-100° C. for 12-48 hours to finally obtain low-dimensional quantum dots; the solid particles are graphite, graphene, molybdenum disulfide, and tungsten disulfide.
9. The method for preparing the low-dimensional quantum dot / nano fluid / solid lubricant composite solid lubricating coating material according to claim 8, characterized in that: The rotation speed of the planetary ball mill is 300-500r / min, and argon gas needs to be introduced into the ball mill for protection. The strong polar solvent is N-methyl-2-pyrrolidone, N,N-dimethylformamide or dimethylacetamide.
10. A low-dimensional quantum dot / nano fluid / solid lubricant composite solid lubricating coating material, characterized in that: The invention discloses a novel nanostructured carbon foam prepared by the preparation method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Self-lubricating composite coating and preparation method and self-lubricating spherical plain bearing and preparation method
CN106047060A
Anti-vibration environmental-protection nano film package material and preparation technology thereof
CN106519483A
Wear-resistant modified PVC-resin nano environment-friendly packaging sheet material and preparation method
CN106519484A
Water-resistant antiseptic paint and preparation method thereof
CN108504220A
High-performance anti-corrosive coating for transformer and preparation method of high-performance anti-corrosive coating
CN108727940A